The The Influence of Educational Level, Employment Status, and Knowledge on Anxiety among Family Planning Acceptors - Yuniarty Yuniarty; Bobby Indra Utama; Elly Usman (GLOBAL HEALTH SCIENCE GROUP, 2026)
Family planning is an effort to regulate the number and spacing of births through the use of contraception in order to achieve family welfare and control population growth. However, anxiety remains a barrier to contraceptive use, often related to fear of insertion procedures and potential side effects, which may increase the dropout rate among acceptors. Therefore, this study aimed to analyze the influence of educational level, employment status, and knowledge on anxiety levels among family planning acceptors. This study employed a quantitative design with a cross-sectional approach involving 100 family planning acceptors selected through purposive sampling. Respondents were recruited during scheduled Posyandu activities and selected based on inclusion and exclusion criteria. Data were collected using structured questionnaires administered through face-to-face guided interviews by the researchers. The data were analyzed using univariate, bivariate, and multivariate methods with ordinal logistic regression. The results showed that most respondents were aged 36–50 years (58.0%), had three children (38.0%), and used three-month injectable hormonal contraception (23.0%). The majority of respondents had a low educational level (84.0%), were unemployed (62.0%), possessed high knowledge levels (57.0%), and did not experience anxiety (48.0%). Bivariate analysis showed significant associations between employment status p = 0.047 and knowledge level p = 0.025 with anxiety levels, while educational level was not significantly associated with anxiety levels p = 0.544. Multivariate analysis indicated that knowledge was the most dominant factor OR = 3.27, followed by employment status OR = 2.86. In conclusion, employment status and knowledge were significantly associated with anxiety levels among family planning acceptors, whereas educational level was not. Health workers, including midwives, are expected to improve education regarding contraceptive methods by providing accurate and comprehensive information to reduce anxiety levels. Midwives should also involve family and social support systems and facilitate open communication regarding complaints during contraceptive use, enabling acceptors to manage anxiety more adaptively.